2023
DOI: 10.1186/s13722-023-00397-8
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine use, quality of life and psychiatric symptom burden in oral and injectable opioid agonist treatment: a cross-sectional study

Maximilian Meyer,
Ferdinand Gygli,
Jean N. Westenberg
et al.

Abstract: Background Use of benzodiazepines (BZD) in patients receiving opioid agonist treatment (OAT) is common and associated with a variety of negative health and social outcomes. This cross-sectional study investigates the impact of BZD use in OAT patients on their quality of life (QoL). Methods A convenience sample of patients receiving oral OAT or heroin-assisted treatment in two outpatient centres in Basel, Switzerland was investigated. Participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…When considering the combination of opioid drugs and sedative drugs, particularly benzodiazepines, it is imperative to exercise a high degree of vigilance due to the potential risks associated with these medications ( Liu et al, 2021 ). Previous studies have confirmed that when compared to using opioids in isolation for managing NP, the combination of opioids and sedative drugs may lead to a notable increase in the risk of drug overdose ( Meyer et al, 2023 ). Furthermore, it can escalate to a critical level, potentially culminating in fatal respiratory depression ( Liu et al, 2021 ).…”
Section: Gut Microbiome and Opioids In Neuropathic Painmentioning
confidence: 97%
“…When considering the combination of opioid drugs and sedative drugs, particularly benzodiazepines, it is imperative to exercise a high degree of vigilance due to the potential risks associated with these medications ( Liu et al, 2021 ). Previous studies have confirmed that when compared to using opioids in isolation for managing NP, the combination of opioids and sedative drugs may lead to a notable increase in the risk of drug overdose ( Meyer et al, 2023 ). Furthermore, it can escalate to a critical level, potentially culminating in fatal respiratory depression ( Liu et al, 2021 ).…”
Section: Gut Microbiome and Opioids In Neuropathic Painmentioning
confidence: 97%